2022
DOI: 10.1029/2021jg006699
|View full text |Cite
|
Sign up to set email alerts
|

Riparian Cottonwood Trees and Adjacent River Sediments Have Different Microbial Communities and Produce Methane With Contrasting Carbon Isotope Compositions

Abstract: Rivers and their adjacent riparian forests are intimately linked by the exchange of water, nutrients, and organic matter. Both riparian cottonwood trees and adjacent river sediments host microbial communities including archeal methanogens, supporting methane production and emission to the atmosphere. Here we combine microbial community and in vitro stable isotope analyses to characterize the drivers of methane cycling in distinct anoxic habitats (river sediments vs. riparian cottonwood stems) associated with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 107 publications
0
3
0
Order By: Relevance
“…Source-tracking analyses revealed a limited contribution of the soil microbiome to the wood microbiome, with estimates that only 3-5% of the community originated from mineral soils and 6-13% from organic soils (SI Figure 5). While expected 93,94 given the pronounced substrate and habitat differences, this result supports a relatively minor role of soil communities in shaping the wood microbiome. In our forest-scale survey, paired soil samples (from both organic and mineral horizons) were collected adjacent to each tree to explore soil origins of the wood microbiome, and whether variations in the wood microbiome were a function of varying soil communities.…”
Section: Minimal Association Of Soil Communities With the Wood Microb...mentioning
confidence: 53%
“…Source-tracking analyses revealed a limited contribution of the soil microbiome to the wood microbiome, with estimates that only 3-5% of the community originated from mineral soils and 6-13% from organic soils (SI Figure 5). While expected 93,94 given the pronounced substrate and habitat differences, this result supports a relatively minor role of soil communities in shaping the wood microbiome. In our forest-scale survey, paired soil samples (from both organic and mineral horizons) were collected adjacent to each tree to explore soil origins of the wood microbiome, and whether variations in the wood microbiome were a function of varying soil communities.…”
Section: Minimal Association Of Soil Communities With the Wood Microb...mentioning
confidence: 53%
“…For example, methanogenic archaea (Methanobacteriales) are highly abundant in sap and heartwoods of various high CH 4 -emitting cottonwoods (Populus sp.) 26,[28][29][30] . In subtropical wetland trees, bark-dwelling methanotrophic bacteria accounted for up to 25% of the total microbial community, and actively mitigated tree stem CH 4 fluxes to the atmosphere by ~30 -40% 31,32 .…”
Section: Introductionmentioning
confidence: 99%
“…In wetland forests, this is particularly important, as soil CH 4 is transported upwards either passively via diffusion, or actively via plant tissues and the transpiration stream, and eventually egressed via tree stems. Studies on the microbial drivers of tree stem CH 4 have also revealed methanogenic communities living within heartwood and living tissues (Feng et al., 2022; Smits et al., 2021; Yip et al., 2019) and also methanotrophic communities within the phyllosphere that is, stems, bark and leaves (Feng et al., 2022; Jeffrey et al., 2021a; Putkinen et al., 2021). Thus, it is clear that methane fluxes from trees can come from diverse sources.…”
Section: Introductionmentioning
confidence: 99%